Maria Nicolas (1906-1938): Black woman, an "outsider within" in the primary public education of Paraná (PerCursos, 2024)
This article outlines aspects of the life trajectory of Maria Nicolas, a primary school teacher based in Curitiba, Paraná, and who conducted classes in primary school in the early decades of the 20th century, covering the period from 1906 to 1938. Employing the lens of intersectionality, the narrative explores various dimensions of her journey, highlighting instances of racial, gender, and class discrimination. The "outsider within", as articulated by Collins (2016) is also examined. The theoretical basis includes Bourdieu's (1996, 2017) concepts of trajectory, habitus, and capital. Nicolas, an alumna of the Escola Normal de Curitiba (Curitiba’s Teacher-Training School) from 1913 to 1916, taught at multiple schools in both metropolitan Curitiba and Paraná’s countryside cities. This professional mobility was intricately linked to the prevailing societal ethos that embraced notions of civility entwined with eugenic and patriarchal ideas of progress. In this context, individuals of the black community, especially women, found themselves in roles still associated with domestic and servile labor. The resistance from white elite women further hindered efforts to transcend racial disparities. As a result, the primary school teacher in focus experienced marginalization, echoing bell hooks’ (2019) notion of living on the margins despite being an integral part of and possessing insight into the larger societal structure.
Keywords: history of education; teacher-training college; public education; black population